Privatization in Yemen : policy and performance / Abdullah Alameer - Alameer, Abdullah (2013)
A major component of economic reform includes the government's withdrawal from the production and service sectors of the economy, including privatization of most public sector enterprises. The main challenge that the government of Yemen faced after a conflict and unification period was to increase the economic growth at the time that government of Yemen inherited the over-centralized public sector. Therefore, an inefficient monopoly and over regulation appeared in public enterprises and restricted many private sector activities. As part of comprehensive economic reforms, the Government of Yemen initiated a privatization program in early 1995 to restructure enterprises towards more efficiency, profitability, and competency. The objectives are to identify privatization methods, problems and obstacles that Yemen faced; to determine the motives and goals of privatization in Yemen; to assess how privatization affects firms‟ profitability, operation efficiency, capital expenditure, output, and employment; and to assess the major problems and constraints the target enterprises encountered at the time-of-handover and explore the major post-privatization restructuring measures adopted. In spite of the presence of some increase in the measured variables, the performance of these enterprises after the privatization process was not better than before the privatization process in the three enterprises examined. The tests of the three profitability variables (return on sale, return on assets, and return on equity) were found to be not significant. The net income efficiency (operating efficiency) indicator was also not significant. The mean difference between the baseline and three years after the follow up privatization for both the capital expenditure to sale, and capital expenditure to assets recorded no significant increase respectively. However, in terms of operating efficiency for sale, the output sale and employment indicators each recorded a significant increase respectively. In conclusion, the findings of this study demonstrate the privatization of these selected enterprises specifically and generally in Yemen was not successful.